2009
DOI: 10.1021/jp9085969
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dots as Nontoxic and High-Performance Fluorescence Imaging Agents

Abstract: Fluorescent carbon dots (small carbon nanoparticles with the surface passivated by oligomeric PEG molecules) were evaluated for their cytotoxicity and in vivo toxicity and also for their optical imaging performance in reference to that of the commercially supplied CdSe/ZnS quantum dots. The results suggested that the carbon dots were biocompatible, and their performance as fluorescence imaging agents was competitive. The implication to the use of carbon dots for in vitro and in vivo applications is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
613
1
16

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 871 publications
(639 citation statements)
references
References 38 publications
9
613
1
16
Order By: Relevance
“…Among them, carbon dots are a new class of functional nanomaterials exhibiting their inherently unique photoluminescent properties, such as wavelengthtuneable emission, excellent solubility, good biocompatibility and chemical inertion [7][8][9][10]. Unlike the semiconductor quantum dots derived from heavy metal precursors incurring long term toxicity [11], C-dots are environmentally friendly and lack of known cytotoxicity [12,13]. The spectroscopic studies have shown that the mixture of C-dots of different sizes with the ability to emit in different color at different excitation wavelength [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, carbon dots are a new class of functional nanomaterials exhibiting their inherently unique photoluminescent properties, such as wavelengthtuneable emission, excellent solubility, good biocompatibility and chemical inertion [7][8][9][10]. Unlike the semiconductor quantum dots derived from heavy metal precursors incurring long term toxicity [11], C-dots are environmentally friendly and lack of known cytotoxicity [12,13]. The spectroscopic studies have shown that the mixture of C-dots of different sizes with the ability to emit in different color at different excitation wavelength [14].…”
Section: Introductionmentioning
confidence: 99%
“…The suggested reason behind the luminescence might be the radiative recombination of the energy-trapping sites on the C-dots surface [7]. In order to enhance the quantum yield (QY) of carbon dots, much effort has been directed toward the use of surface passivation method to achieve a strong photoluminescence [13]. Doping C-dots with inorganic salt ZnS or SiO 2 is able to enhance the QY of C-dots [10].…”
Section: Introductionmentioning
confidence: 99%
“…The CDs were found to have emission in the visible region when they are passivated by polymer chains [148] , doped with inorganic salts or photosensitizer [59, 149 -152] . These materials are being investigated for optical imaging agents using both one-and twophoton excitation [153] . Despite the fact that small animal or thin tissue imaging has been largely illustrated, clinical applications have not been yet proven.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…Therefore, exploring novel fluorescence probes to address these limitations and finding new available fluorescence tags as potential bioimaging probes is important. [11,12] Natural sources, such as plants, have evolved many important traits, which we sought to exploit for novel applications. [13][14][15] In addition to water solubility, potential applicability to biological systems requires demonstrated clinical safety.…”
Section: Introductionmentioning
confidence: 99%